(untitled) (International journal of artificial intelligence, 2024)
Bread fermentation and softening are the classic methods of making fur skins and have been used for a long time in the processing of the entire range of raw fur, as they provided the highest quality leather fabric. For fermentation of purebred karakul dry-salted canning, the test of milk whey obtained from dairy waste containing lactic acid may be of practical interest.